The degree to which the Hussein labor and construction camps contribute to the development of the self-esteem of the participants in Jordan - Alakili, Hamzeh Said; Tahayneh, Zaid (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the degree of the contribution of Al-Hussein camps for work and construction in developing the self-esteem of the participants according to the variables of gender and region, and the researchers used the descriptive approach for its suitability to the nature of the study. The Al-Hussein labor and construction camps in developing the self-esteem of the participants were high. The results also showed that there were no statistically significant differences in self-esteem due to the gender variable (male - female). The results also indicated that there were no differences in the level of self-esteem attributable to the variable of the region (north, center and south) in all areas of self-esteem except for the field of "self-affirmation" in which statistically significant differences appeared in favor of the northern region.In light of the findings of the study, the two researchers recommend increasing attention to the topic of self-esteem among young people participating in the activities and programs of Al-Hussein camps for work and construction, through the Ministry of Youth taking the necessary measures to raise the level of self-esteem of the participants and create the appropriate atmosphere to achieve this goal. And holding programs and activities that provide young men and women with the necessary skills that contribute to the development and strengthening of their self-esteem.
Keywords: self-esteem; self-esteem development; Al-Hussein camps